Audience Reception Researches, Significance Of Involvement And Reception Patterns - Lalidji, Mohamed Amine (جامعة الوادي - University of Eloued, 2023)
The aim of this intervention is to point out the importance of two concepts in audience reception research which symbolize audience activity. The first concept is involvement and the second is reception patterns, we shed the light on various decoding models by analyzing the leading researches to understand audience interpretations of media content. We concluded that audience involvement and reception patterns carry different meanings and levels, which requires dealing with it theoretically and procedurally as a multi-dimensional variable and not a unified entity, this without underestimating the power of cultural producers and their role in framing audience interpretations.
مقال
Keywords: reception ; involvement ; audience ; reception patterns